The Effectiveness of Pure Honey as Antioxidant and Gastroprotective in Sprague Dawley Rats (Rattus novergicus) - Tanny, Sesilia Bella; Sumbayak, Erma Mexcorry; Dewajanti, Anna Maria; Rumiati, Flora (Jurnal MedScientiae, 2024)
Gastritis is a condition where inflammation occurs in the surface lining of the stomach which can be caused by several factors, one of which is non-steroidal anti-inflammatory drugs or NSAIDs. The most commonly used NSAIDs are aspirin, aspirin at a dose of 600 mg/kg can cause acute damage to the stomach. Honey with 30 ml/day or the equivalent of 2 tablespoons provides a gastroprotective effect or protection and healing for stomach damage because it contains antioxidants which reduce the level of damage to the stomach. The purpose of this study was to determine the antioxidant and gastroprotective effectiveness of pure honey in Rattus norvegicus Sprague Dawley rats induced by oral aspirin. This study used a laboratory experimental method which examined the effectiveness of pure honey as an antioxidant and gastroprotective for 11 days. The subjects used were 25 Rattus norvegicus. The results showed that based on histopathological scores, administration of 0.5 mL/kgBB honey for 4 days in experimental animals could significantly reduce gastric damage induced by aspirin 600 mg/kgBB. However, when viewed from the results of the data on GSH levels, there was no significant effect of giving honey on GSH levels in experimental animals.